The Penguin book of haiku - Kern, Adam L. (UK : Penguin Books, 2018)
Now a global poetry, the haiku was originally a Japanese verse form that flourished from the sixteenth to nineteenth centuries. Although renowned for its minimalism and brevity, usually running three lines in seventeen syllables, and by its use of natural imagery to make Zen-like observations about reality, in fact the haiku is much more: it can be erotic, funny, crude and mischievous. Presenting over a thousand exemplars in vivid and engaging translations by Adam L. Kern, this anthology offers an illuminating introduction to this widely celebrated, if misunderstood, art form.
Includes index.
Keywords: Haiku -- Translations into English; Japanese poetry -- Translations into English; Haiku; Japanese poetry; Translations